The Construction of Meaning Through the Visual Images and Written Texts in Nature Republic - Wendy Cynthia Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2020)
Advertisement is an important business tool that enables companies to promote their products, as well as delivering a message. In this research, I use Nature Republic posters entitled “Soothing Gel” and “Soothing & Moisture Aloe Vera 90% Body”. I used qualitative approach in this research. Next, I use the theories of Multimodal Discourse Analysis for the first research question and Denotative and Connotative for the second research question. I aimed to discover what the meanings that are constructed through the visual images and how the meanings are supported by the written texts. Through the poster, Nature Republic is building the feelings of being beautiful, young, confident, natural, pure, and trustworthy to its consumers. In conclusion, Nature Republic is trying to make consumers believe in their products and deliver many values through its posters. Keywords: Advertisement, marketing, poster, multimodal discourse analysis, denotation, connotation.